Common Time: Embedding the concept of academic and social integration across cognate degree programmes - Fowler, J.; Zimitat, Craig (Routledge, 2008)
Common Time (CT) was a structured programme designed to enhance the social and academic engagement of a growingly diverse student body on a new campus that draws its population from a low-socioeconomic area. As a voluntary and non-remedial programme, it incorporated a range of formal and informal activities and processes to engage students. CT operates across degree programmes and involves the collaboration of academics, librarians and support staff such as learning advisers. Interviews with students reveal that the CT strategy achieved the objectives for which it was designed: to facilitate faculty-student informal interaction, provide the opportunity for students to interact and develop relationships with their peers, and provide a range of activities that would assist students with their academic and intellectual development. Further evidence of its success is borne out by high and consistent attendance, the longevity of the programme and its adoption as a model at other institutions.